2019
DOI: 10.1186/s13018-019-1298-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bilateral decompression via unilateral laminotomy and conventional laminectomy for single-level degenerative lumbar spinal stenosis regarding low back pain, functional outcome, and quality of life - A Randomized Controlled, Prospective Trial

Abstract: Background Conventional posterior open lumbar surgery is associated with considerable trauma to the paraspinal muscles. Severe damage to the paraspinal muscles could cause low back pain (LBP), resulting in poor functional outcomes. Thus, several studies have proposed numerous surgical techniques that can minimize damage to the paraspinal muscles, particularly unilateral laminotomy for bilateral decompression. The purpose of this study is to compare the degree of postoperative LBP, functional outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 25 publications
(25 reference statements)
1
42
1
Order By: Relevance
“…Many studies have reported on comparable short and longterm favorable clinical outcomes between open facet sparing laminectomy and minimally invasive ULBD in lumbar central and lateral recess stenosis. [29][30][31] The benefit extends even to lumbar stenosis cases with spondylolisthesis. 32 Additionally, there are also several studies describing similar favorable results bewww.e-neurospine.org S95 tween microsurgical or tubular techniques of ULBD and endoscopic lumbar decompression in the setting of lumbar stenosis, with shorter hospital stay and less collateral tissue injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported on comparable short and longterm favorable clinical outcomes between open facet sparing laminectomy and minimally invasive ULBD in lumbar central and lateral recess stenosis. [29][30][31] The benefit extends even to lumbar stenosis cases with spondylolisthesis. 32 Additionally, there are also several studies describing similar favorable results bewww.e-neurospine.org S95 tween microsurgical or tubular techniques of ULBD and endoscopic lumbar decompression in the setting of lumbar stenosis, with shorter hospital stay and less collateral tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported on comparable short and long-term favorable clinical outcomes between open facet sparing laminectomy and minimally invasive ULBD in lumbar central and lateral recess stenosis [ 29 - 31 ]. The benefit extends even to lumbar stenosis cases with spondylolisthesis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The backbone is divided to thoracic (T1-T12), cervical (C1-C7), sacroiliac (S-Fused) and lumbar areas (L1-L5) as well as coccyx (4 fused). Literature review shows that the main cause of low back pain is degenerative spinal stenosis [14]. It is considered as one of the most common indices of spinal surgery which leads to tumor and spinal dislocation.…”
Section: Figure1 Structure Of the Vertebral Bodymentioning
confidence: 99%
“…As shown in equations (11) and (12), the covariance matrix is determined from a block covariance matrix to determine the difference in the variance points of the vertebral region as shown in Figure 5. As shown in Figure 5, the eigen decomposition of equation 12is obtained from equation (14) which allows the eigen values ⋀ l|k and eigen vectors φ l|k that depicts the conditional variability k l  in accordance with Eigen time factor between shapes y j,l and y j,k , with more and less distortion points during segmentation which helps to evaluate the ROC for the image. The Yellow region shows good ROC point prediction using variance analysis, Further the conditional models are represented as follows:…”
Section: Preposition 2: Statistical Vertebral Decomposition and Imagementioning
confidence: 99%
See 1 more Smart Citation